Sustaining peace in ASEAN and the Asia-Pacific preventive diplomacy measures - Puja, I Gusti Agung Wesaka; Yanjun, Guo (Singapore World Scientific Publishing Co. Pte. Ltd., 2023)
"In 2016, the United Nations (UN) General Assembly and the UN Security Council respectively adopted resolutions on the review of the UN peacebuilding architecture, and the concept of "sustaining peace" was formally presented. Since then, the "sustaining peace" agenda has gradually become the core strategy of the peace cause of the UN. The agenda for sustaining peace emphasizes capacity-building for conflict prevention at the regional level. Faced with the escalation of the international security challenge, regional organizations are increasingly playing a prominent role. They have become important participants in the international peace and security agenda by enhancing cooperation with the UN. The Association of Southeast Asian Nations (ASEAN), as the centre of regional cooperation processes in the Asia-Pacific, established a series of norms and instruments related to conflict prevention. This book intends to promote discussions on linking conflict prevention and/or preventive diplomacy activities in the region with the sustaining peace agenda promoted by both the ASEAN on a regional scale and the UN on a global scale. In a collaboration between the ASEAN Institute for Peace and Reconciliation (ASEAN-IPR) and China Foreign Affairs University (CFAU), the book provides discussions from the perspective of both Chinese as well as ASEAN scholars on traditional, as well as emerging, topics on sustaining peace, as well as conflict prevention, conflict management, and conflict resolution"-- Provided by publisher.
Keywords: ASEAN; Conflict management -- Pacific Area; Conflict management -- Southeast Asia; Peace-building -- Pacific Area; Peace-building -- Southeast Asia; Pacific Area -- Politics and government; Southeast Asia -- Politics and government